“Instruction a Torment”? Jane Austen’s Early Writing and Conflicting Versions of Female Education in Romantic-Era “Conservative” British Women’s Novels - Bagchi, Barnita (Romanticism on the Net, 2005)
AbstractAusten’s juvenilia is a fruitful entry point into the late-eighteenth- and early-nineteenth-century field of “conservative” female-authored fiction centred on the development and education of adult or near-adult women. Austen is, in her treatment of female education, a highly revisionist conservative, but also, in terms of adventurousness, range of ideas, and ambitions, much more conservative than public-minded conservative writers of the 1790s, such as Clara Reeve, or some of Austen’s own contemporaries, such as Mary Brunton. It is also possible to argue that Austen’s deep scepticism about the pressures of education as ideology operating on women makes her, by a double turn, not a conservative writer. The instability and unviability of radical and conservative as categories in opposition to each other in the context of Romantic-era British women’s writing is now recognized. However, it has not been recognized that this unviability has significant consequences for our understanding of Romantic-era, female-authored fiction about female education. Tensions and instabilities mark out the female novelistic field in this period. This field is far more of an unhomogenized, patchwork arena than has been supposed, and it does not lead to the clear-cut definition of a hegemonic, bourgeois domestic female subjectivity. The narrative is far more complex, and it is misleading to reduce to a linear model the curves, fluctuations, contradictions, and possibilities for female development found in Austen’s early treatments of female education, as well as in fiction by other contemporary or near-contemporary, bold, disturbing, adventurous, “conservative” delineators of female development such as Reeve or Brunton.